Analisis Praktik Pembagian Nasi Box pada Hari Senin dan Kamis di Masjid Jagalan Kudus: Studi Living Qur’an Q.S. Yunus: 57 - Amir Syarifudin; Ma’mun Mu’min (el Buhuth: Borneo Journal of Islamic Studies, 2026)
This article aims to analyze one of the phenomena that occurred at the Jagalan Mosque, Kudus, namely the rice box intended for the congregation. This study seeks to explore the origins of the distribution of free rice boxes and also analyze the practice of distributing free rice boxes at the Jagalan Kudus Mosque. The research used is a qualitative research with the type of field research, the data collection techniques used are direct observation in the field and conducting interviews with several parties, and the theory used is the theory of maslahah by Imam Al-Ghazali. The results of this study are the first, The practice of distributing free rice boxes at the Jagalan Mosque reflects solidarity and social concern in Islam, started in 2016 as a noble effort to honor the congregation, especially online motorcycle taxi drivers, and continues to this day thanks to the support of local donors and social media, in line with the teachings of the Qur'an which emphasizes the benefits and blessings for humanity. Second, a study of the living Quran at the Jagalan Mosque shows that the practice of distributing free rice boxes every Monday and Thursday not only reflects the application of Quranic values ​​in daily life, but also plays a role in building togetherness and social solidarity, as expressed by the congregation and online motorcycle taxi drivers who feel the direct benefits of this practice.